Associativismo e participação política: uma análise das associações comunitárias rurais de Feira de Santana-Bahia - Martins, Martinez Santos (2019)
This work has as main objective to analyze the relation between associativism and political participation in the rural community associations of Feira de Santana, Bahia. Political participation has been considered by the political literature as an essential variable to measure the quality of democratic regimes and to understand the characteristics and specificities of social agents in different socioeconomic realities. Data collection was done through a questionnaire applied to the members of selected entities according to the following criteria: they are in agreement with the New Regulatory Framework of Civil Society Organizations (Law 13.019 / 14), have collective production activity, and be in full activity. In addition, an interview was conducted with all representatives of the associations surveyed in order to apprehend perceptions about the importance of community association. The data examined lead to the affirmation that the Feira voters who participate in rural community associations have attributes that explain the persistence of the social agents in the strengthening of a political culture with values relevant to the associativism, therefore a concern with the diverse collective issues and with the improvement of participatory democracy.